Lumbar spine injury in rowing: the influence of spinal kinematics, rowing mode and fatigue - Wilson, Fiona (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Physiotherapy, 2011)
Rowing is a sport which requires high volumes of training to compete at elite levels. Studies over recent years have noted an increase in the number of lumbar spine injuries reported by this population; however limitations in data reported to date means that the exact extent of this problem and the associated factors, are not well understood. Therefore, the overall aim of this study was to determine if lumbar spine injury is a specific problem in rowers and to establish how kinematic variables of the lumbar spine relate to this.
Keywords: Physiotherapy, Ph.D.; Ph.D. Trinity College Dublin